Encephalopathy caused by ablation of very long acyl chain ceramide synthesis may be largely due to reduced galactosylceramide levels* - Ben-David, Oshrit; Pewzner-Jung, Yael; Brenner, Ori; Laviad, Elad L.; Kogot-Levin, Aviram; Weissberg, Itai; Biton, Inbal E.; Pienik, Reut; Wang, Elaine; Kelly, Samuel; Alroy, Joseph; Raas-Rothschild, Annick; et al. (The journal of biological chemistry, 2011)
Sphingolipids (SLs) act as signaling molecules and as structural components in both neuronal cells and myelin. We now characterize the biochemical, histological, and behavioral abnormalities in the brain of a mouse lacking very long acyl (C22-C24) chain SLs. This mouse, which is defective in the ability to synthesize C22-C24-SLs due to ablation of ceramide synthase 2, has reduced levels of galactosylceramide (GalCer), a major component of myelin, and in particular reduced levels of non-hydroxy-C22-C24-GalCer and 2-hydroxy-C22-C24- GalCer. Noteworthy brain lesions develop with a time course consistent with a vital role for C22-C24-GalCer in myelin stability. Myelin degeneration and detachment was observed as was abnormal motor behavior originating from a subcortical region. Additional abnormalities included bilateral and symmetrical vacuolization and gliosis in specific brain areas, which corresponded to some extent to the pattern of ceramide synthase 2 expression, with astrogliosis considerably more pronounced than microglial activation. Unexpectedly, unidentified storage materials were detected in lysosomes of astrocytes, reminiscent of the accumulation that occurs in lysosomal storage disorders. Together, our data demonstrate a key role in the brain for SLs containing very long acyl chains and in particular GalCer with a reduction in their levels leading to distinctive morphological abnormalities in defined brain regions.
Gesehen am 16.03.2022